2019
DOI: 10.1371/journal.pgen.1008485
|View full text |Cite
|
Sign up to set email alerts
|

The impact of genetic adaptation on chimpanzee subspecies differentiation

Abstract: Chimpanzees, humans’ closest relatives, are in danger of extinction. Aside from direct human impacts such as hunting and habitat destruction, a key threat is transmissible disease. As humans continue to encroach upon their habitats, which shrink in size and grow in density, the risk of inter-population and cross-species viral transmission increases, a point dramatically made in the reverse with the global HIV/AIDS pandemic. Inhabiting central Africa, the four subspecies of chimpanzees differ in demographic his… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(67 citation statements)
references
References 87 publications
(149 reference statements)
8
59
0
Order By: Relevance
“…ellioti and P.t. troglodytes ( 10 , 36 ). Coupled with our results, we find evidence that selection has been a major driver for differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ellioti and P.t. troglodytes ( 10 , 36 ). Coupled with our results, we find evidence that selection has been a major driver for differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA preprocessing with significant enrichment of signals of selection indicating that regulatory regions are significant targets in driving adaptation). Demographic models used here are based on ( 10 ) and adapted to take into account meaningful admixture events and long-term effective population size differences between subspecies; however, it is worth mentioning that the robustness of our scan is sensitive to any misspecified demography [see ( 51 ) for a discussion]. Our statistical framework used neutral and positive selection to train the random forest algorithm using different selection times and coefficients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used summary statistics based on the widely used comparison between neutral mutations, labelled here ENVs (Evolutionary Neutral Variants), and mutations potentially targeted by selection, labelled PSV (Possibly Selected Variants), e.g., synonymous and non-synonymous comparison (Kimura 1977; Mcdonald and Kreitman 1991). Our rational was motivated by previous studies showing that positive selection causes genome-wide excesses of candidate SNPs of selection (i.e., those with extreme values for a given neutrality statistic) within or nearby genes relative to intergenic regions (e.g., coding SNPs or cis -acting eQTLs vs intergenic SNPs (Voight, et al 2006; Frazer, et al 2007; Barreiro, et al 2008; Kudaravalli, et al 2009; Jin, et al 2012; Fagny, et al 2014; Schmidt, et al 2019)). In such studies, the ENV SNP class is the neutral baseline used to control for false discoveries (similar rates of false positive are expected across SNP classes (Barreiro, et al 2008)).…”
Section: Resultsmentioning
confidence: 99%
“…Recent efforts to sequence diverse great ape genomes have led to identification of signatures of natural selection using SNV data that may help to explain features unique to chimpanzee species and subspecies [5,32,45,73]. To understand if our identified SVs might impact the outcome of such studies or explain signatures of selection previously identified, we compared our map of SVs with a recent study of natural selection in multiple genomes of the four chimpanzee subspecies (Pan troglodytes verus, troglodytes, ellioti, and schweinfurthii) mapped to the human reference genome [45].…”
Section: Genes Showing Signatures Of Natural Selectionmentioning
confidence: 99%